2SPD-005 New closed system transfer device contains real drug vapours for up to 28 days. Issue 1 (23rd March 2023) - Navarro, D; Epstein, D; Raz, O; Slutsky Smith, E
Abstract : Background and Importance: Several Closed System Transfer Devices (CSTDs) are currently approved a 7-day usage period. Increasing pressure to reduce drug costs and data supporting stability of some drugs beyond 7 days create a demand for CSTDs that contain hazardous drug vapours for 28 days. A previous study proved that a model air-cleaning CSTD contains drug vapours for 7 days. Aim and Objectives: The aim was to test drug vapour containment of an air-cleaning CSTD under extreme conditions for 28 days. Material and Methods: Cyclophosphamide (CP) was chosen as the representative drug. A model CSTD (Chemfort™) Vial Adaptor (VA) was connected to each vial, and CP was reconstituted using the CSTD Syringe Adaptor. VAs at the end of their shelf life, representing extreme conditions, were tested both immediately following and 28 days after reconstitution, with and without intact Toxi-Guard ® air-cleaning systems (an integral part of the Chemfort TM VA). Each vial was transferred to a closed test chamber connected to a vapour trap. To increase drug vapourisation, the chamber was heated to 50°C and nitrogen gas was constantly introduced into the vials. Any vapours potentially released from the Chemfort™ VA were trapped and then extracted with solvent. Quantification of CP was performed using a validated LC/MS/MS method. Results: No CP was detected for any of the VAs with intact Toxi-Guard® components, whether tested immediately or 28 days after reconstitution, even when heat and gas flow were employed to encourage the production of vapours and when the VA was at the end of its shelf life. The limit of detection of the method was estimated at 0.02 ng. Without an intact Toxi-Guard®, 110.3 ng of CP were released into the environment. Conclusion and Relevance: The model CSTD utilising Toxi-Guard ® air-cleaning technology contained drug vapours after a 28-day usage period, even under extreme conditions. A recent study proved 28-day prevention of microbial ingress by the same CSTD. Taken together, the two studies support pharmacists' decision to use drugs for their full shelf life or to extend the beyond-use-date up to 28 days when using an appropriate CSTD, thus reducing cost and waste. References and/or Acknowledgements: Conflict of Interest: Corporate sponsored research or other substantive relationships: Ofer Raz and Elana Slutsky Smith are employed by Simplivia Healthcare Ltd, the manufacturer of Chemfort TM . Dekel Navarro and Daniel Epstein declare no conflict of interest relating to the material presented in the abstract. Funding for this project was provided by Simplivia Healthcare Ltd, the manufacturer of Chemfort TM .